Appropriateness applied: a renewed coaching perspective to reach out to every athlete - Ramos, A.; Ribeiro, J.; Afonso, J.; Mesquita, I. (International Sport Coaching Journal, 2025)
Beyond teaching models/approaches, currently sports coaching literature is lacking on conceptual frameworks that offer a pedagogical structure capable of being adjusted and applied (i.e., appropriated) to athletes` needs and diverse sport contexts. The Appropriateness Framework (AF) is a pedagogical structure to help sport practitioners in building meaningful learning environments while respecting inter- and intraindividual variations throughout the learning process. The innovative character of the AF relies on integrating simultaneously well-known and widespread concepts and principles from sports pedagogy and coaching, as well as extending the concept of representativeness to athletes` features and motivations. This practical advance article aims to present the AF, namely their conceptual pillars (i.e., premises) and sequential procedures of operationalization (i.e., steps), as well as to exemplify how it can be used through practical cases. From a theoretical viewpoint, the application of AF is independent of any teaching model and/or specific athlete-centered approach. Thus, from a practical standpoint, this paper represents a guideline for coaches adopting process-oriented learning perspective that might be applied in several sport contexts and potentiates the "reaching out" of every athlete.